The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1023/b:astr.0000045036.76044.bd
|View full text |Cite
|
Sign up to set email alerts
|

On The Internal Structure Of Starless Cores. Physical and Chemical Properties of L1498 and L1517B

Abstract: Context. Low mass starless cores present an inhomogeneous chemical composition. Species like CO and CS deplete at their dense interiors, while N2H + and NH3 survive in the gas phase. As molecular line observations are used to determine the physical conditions and kinematics of the core gas, chemical inhomogeneities can introduce a serious bias. Aims. We have carried out a molecular survey towards two starless cores, L1498 and L1517B. These cores have been selected for their relative isolation and close-to-roun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 82 publications
6
36
0
Order By: Relevance
“…However, in starless cores the values are not likely to be much higher (Hotzel et al 2001;Tafalla et al 2002;Crapsi et al 2007). Tafalla et al (2004) found that the excitation temperatures of the (1, 1) and (2, 2) lines varied by a factor of several. This variation depends on several factors, the cloud optical depth, the volume density, and the variation of the kinetic temperature.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in starless cores the values are not likely to be much higher (Hotzel et al 2001;Tafalla et al 2002;Crapsi et al 2007). Tafalla et al (2004) found that the excitation temperatures of the (1, 1) and (2, 2) lines varied by a factor of several. This variation depends on several factors, the cloud optical depth, the volume density, and the variation of the kinetic temperature.…”
Section: Discussionmentioning
confidence: 93%
“…However, in the modelling of the NH 3 spectra, the fractional abundance of para-NH 3 is always kept at a constant value of 10 −8 (e.g. Hotzel et al 2001;Tafalla et al 2004). This applies also to the χ-model.…”
Section: Core Modelsmentioning
confidence: 99%
“…Subsonic turbulence contributes less to the energy budget of the cloud than thermal pressure and so cannot provide sufficient support against gravitational collapse (Myers, 1983;Goodman et al, 1998;Tafalla et al, 2006). If cores are longer lasting entities there must be other mechanisms to provide stability.…”
Section: Star Formationmentioning
confidence: 99%
“…In the calculation of total ammonia column density we assumed the NH 3 ortho-to-para ratio to follow the LTE conditions. The kinetic temperature of the gas was calculated from the rotational temperature using the semiempirically derived analytic expression from Tafalla et al (2004) …”
Section: Ammonia Column Densities and The Kinetic Temperatures Using mentioning
confidence: 99%